Assessment of doctor’s satisfaction with governmental hospital after the war 2024 in Sudan - Omer, Ali (International Journal of Medical Students, 2025)
BACKGROUND: After the war in Sudan, and especially after the occupation of the city of Madani, a large number of people were displaced to the city of Port Sudan, including doctors. There was great pressure on government hospitals in Port Sudan and therefore doctors. METHOD: This is a descriptive cross-sectional study to develop and validate a self-administered doctor’s satisfaction survey. This study was conducted based on a literature review from published literature from google scholar, PubMed, journals and for finding relevant information from WHO and UNICEF websites. The data have been collected through a designed questionnaire via Google form consists of 9 multiple choices questions, 4 questions measured on a 5-point Likert scale and 2 short answer questions. The questionnaire has been spread to doctors in governmental hospitals in Port Sudan. The data collected analyzed statistically by google form. RESULTS: The outcome from our analyzed data and findings that female to male ratio is ( 1:1), most of them from (20-30) and (30-40) age groups represented in (70.8%) and (29.2%) respectively. (37.5%) are Refugees from other states and Khartoum represents (36.4%) from the total. The majority of them in the beginning of their career, "houseman" representing (41.7%) followed by (33.3%) are registrar, then general practitioners by (12.5%) and lastly specialists by (8.3%). Only (8.3%) have 6-9 years’ experience in hospital, 3-6 years’ experience by (12.5%), 1-3 years’ experience by (29.2%) and less than 1-year experience represents the most by 45.8%. Satisfaction of Doctors [From 1-5 (1 represents the lowest and 5 is highest)] (62.5%) give scale (1/5) the lowest to salary, (33.4%) are ok with work time, (41.6%) are not satisfied from the work experience (give scale 2/5), (70.8%) are not satisfied from the learning methods, only (1.6%) are satisfied from hospital environment, no (5/5) response in hospital cleaning, (75%) agreed on there is low safety equipment’s, only (20.8%) are satisfied from the work place, (58.3%) are not satisfied from work schedule and (50%) are not satisfied from working hours (given scale 2/5 and 1/5), (62.5%) give (1/5) and not satisfied at all from hospital sanitation, for work over load (91.6%) are suffering, (37.5%) are satisfied from doctor patient relationship and (75%) are satisfied from hospital colleagues. Overall satisfaction is (16.6%).• Training experience beneficiary out of 5 (5 represents the highest and 1 represents the lowest), (4.2%) give scale (5/5), while (41.7%) give (3/5) and (29.2%) give (4/5) and (1/5 - 2/5) scales represents (12.5%) for both.• (66.7%) agreed with that doctors stick to federal ministry of health guidelines in treatment while (29.2%) are dis agree.• unfortunately (27.3%) see that current low can prevent their rights on the other hand (31.8%) they Don't see that and (40.9%) are not sure. CONCLUSION: The Doctors are not satisfied, and they aspire to increase salaries, provide all supplies and medicines for emergency cases, provide facilities and equipment, take care of the hospital environment, continuous training for doctors, and create a good work environment while preserving all their rights.